KAJIAN PERAN LEMBAGA DAN KEARIFAN MASYARAKAT DALAM PENGELOLAAN EKOSISTEM HUTAN MANGROVE SECARA TERPADU DI DELTA MAHAKAM - , Lenny Dianawati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
At this time the mangrove forest in Delta Mahakam region heavily damaged area of 24 035 hectares or 49.44% of the mangrove area in the Delta Mahakam, covering an area of 41 608 hectares lightly damaged or 27.78% of the mangroves in the Delta Mahakam, and is still in a state of an area of 34 089 hectares only good or 22.7% of the mangrove area in the Delta Mahakam. Such damage is mostly caused by the opening of mangrove forests for aquaculture enterprises by people from outside the region of East Kalimantan. Law No. 41 of 1999 mandates that the Forest Service has the authority to preserve the mangrove forests in the waters include waters in the Delta Mahakam. On the other hand, the Law Number 31 of 2004 on Fisheries requires that fishery management area of the Republic of Indonesia for fishing or fish pembudiyaan include rivers, lakes, reservoirs, marshes and other stagnant water that can be cultivated and land fish farming potential in the territory of the Republic of Indonesia. Of the problems of overlapping authority and these regulations, each sector has its own laws, so that each sector also has its own authority. Mangrove forest is not entirely the responsibility of the government alone but required the participation of the community in the Delta Mahakam Region to achieve sustainability of integrated mangrove forests. Researchers used a qualitative descriptive approach to present the existing problems based on field data on the management of mangrove forests in the area of the Delta Mahakam. This research was conducted in the Delta Mahakam, East Kalimantan Province. Tools and materials used in this research is to guide the interview, observation, documentation, cameras, and tape recorders. How to include the data analysis phase of data reduction, data display, and conclusion drawing or verification. Based on the research and discussion that has been done, it was concluded that: (1) The management of mangrove forest in Delta Mahakam itself involves the role of public, private, and government. Relevant authorities are the Environment Agency East Kalimantan, East Kalimantan Provincial Forestry Office, and the Department of Fisheries and Marine Resources in East Kalimantan province. Parties divided into indigenous communities and migrants. The indigenous people living around the Delta Mahakam mangroves perform maintenance activities, planting, mangrove forests and environmental cleanup. While the immigrant communities who are entrepreneurs add provide some funds for the government managed to improve the condition of the Mahakam Delta mangrove forests damaged by farming activities. (2) Integration between the government and indigenous communities and migrant communities as a farm employer is required to ensure the implementation of the protection, preservation, and utilization of mangrove ecosystems as resources in coastal areas, life support systems, and high-value natural resources